Explaining environmental health behaviors: Evidence from rural India on the influence of discount rates - Atmadja, S.; Sills, E.O.; Pattanayak, S.K.; Yang, J.C. (Cambridge University Press, 2017)
The authors examine whether high personal discount rates help explain why and which households in developing countries under-invest in seemingly low-cost options to avert environmental health threats, including bednets, clean cooking fuels, individual household latrines, water treatment and handwashing. First, the authors elicit personal discount rates by combining a simple randomized experiment with detailed surveys of over 10,000 rural households in Maharashtra, India. Personal discount rates are lower for women, for better-off households, and for households who can access formal credit. Secondly, they show that the discount rate is negatively related to a suite of behaviors that mitigate environmental health threats, from very low-cost steps like washing hands to more significant investments like household latrines, even after controlling for socio-economic status, access to credit, public infrastructure and services, and relevant beliefs.